Caring for and Preserving the Environment: Christian Rights and Responsibilities to ‘The Creator’ - Hutahaean, Hasahatan; Hutahaean, Patricia Karina (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2026)
This research examines environmental ethics in Christian theology, highlighting human responsibility towards God's creation. In the modern era, the ecological damage caused by human activities has become a serious concern related to the moral obligations outlined in the Bible, which states that humans are entrusted to manage and care for creation, even though this practice is often neglected. This article is compiled using qualitative methods through a literature review approach. The aim is to explore how Christian teachings can integrate environmental awareness into the daily lives of believers. The research findings indicate that a deep understanding of creation and human responsibility as stewards can lead to collective action for environmental sustainability. This research is expected to be a source of inspiration for the Christian community to actively contribute to preserving creation for the well-being of future generations. Therefore, environmental ethics is not just a moral issue, but also an integral part of faith that must be manifested in tangible actions.